Settlement of Criminal Cases Through the Angkon Muakhi Customary Law of Lampung as a Form of Restorative Justice from a Human Rights Perspective - Zainudin Hasan; Fathul Muin (As-Siyasi: Journal of Constitutional Law, 2026)
This study examines the settlement of criminal cases through the integration of the customary legal values of Angkon Muakhi in Lampung Province from a human rights perspective. The Angkon Muakhi tradition, rooted in the Lampung community's values of brotherhood, serves not only as a social bond but also as a restorative justice mechanism for resolving conflicts and criminal acts through reconciliation and peace. The purpose of this study is to analyze the application of Angkon Muakhi as a non-penal case-resolution model aligned with the principles of restorative justice and human rights, emphasizing respect for dignity, equality, and social harmony. This study uses a juridical-normative and empirical approach, combining literature studies and field interviews with traditional leaders (penyimbang and perwatin adat) in various districts in Lampung. The results show that Angkon Muakhi effectively restores social relations and societal balance through the principles of peace, kinship, and moral responsibility, without relying on criminal sanctions. This study concludes that integrating Angkon Muakhi values into the Indonesian criminal justice system can strengthen the protection of human rights, foster social harmony, and serve as a model of restorative justice rooted in local culture